Study of Chromium Removal by the Electrodialysis of Tannery and Metal-Finishing Effluents - Ruan C. A. Moura; Daniel A. Bertuol; Carlos A. Ferreira; Franco D. R. Amado (International Journal of Chemical Engineering)
The metal-finishing and tannery industries have been under strong pressure to replace their current wastewater treatment based on a physicochemical process. The electrodialysis process is becoming an interesting alternative for wastewater treatment. Electrodialysis is a membrane separation technique, in which ions are transported from one solution to another through ion-exchange membranes, using an electric field as the driving force. Blends of polystyrene and polyaniline were obtained in order to produce membranes for electrodialysis. The produced membranes were applied in the recovery of baths from the metal-finishing and tannery industries. The parameter for electrodialysis evaluation was the percentage of chromium extraction. The results obtained using these membranes were compared to those obtained with the commercial membrane Nafion 450.